Fake Product Review Monitoring & Removal and Sentiment Analysis of Genuine Reviews - Abhishek Punde; Sanchit Ramteke; Shailesh Shinde; Shilpa Kolte (International Journal of Engineering and Management Research, 2019)
Any E-Commerce website gets bad reputation if they sell a product which has bad review, the user blames the e- Commerce website rather than manufacturers most of the times. In some review sites some great audits are included by the item organization individuals itself so as to make so as to deliver false positive item reviews. To eliminate these type of fake product review, we will create a system that finds out the fake reviews and eliminates all the fake reviews by using machine learning. We also remove the reviews that are flood by a marketing agency in order to boost up the ratings of a particular product .Finally Sentiment analysis is done for the genuine reviews to classify them into positive and negative. We will use Bag-of-words to label individual words according to their sentiment.